Work experience and competence as indicators of performance effectiveness of editors in book publishing firms in Southwestern Nigeria (2023)
Performance effectiveness of editors is critical to every Publishing firm. For editors to discharge their duties efficiently, editorial competence is crucial. It is in the light of this that this study examined how work experience and competence indicate performance effectiveness of editors in book Publishing firms in southwestern Nigeria. Descriptive survey research method was adopted, structured questionnaire tagged "WECIPEE" was the instrument, while four research questions were raised. The population of the study was the editorial staff of the 139 registered Publishing firms in southwestern Nigeria while random sampling technique was used to select the editors of twenty-four Publishing Companies which constituted the study sample. The data collected was analysed using percentages and Statistical mean. Findings show that publishers preferred editorial staff who have adequate experience, and that human capacity development enhanced performance effectiveness of editors. The study recommended that publishers should emphasise editors' competence, ICT skills, and training.